Light-driven secondary structural remodeling in biomimetic nanosystem to enhance tumor chemo-phototherapy - Weijie Wang; Chenguang Sun; Linhao Jing; Yaning Xia; Shuijun Zhang; Yupeng Shi (Materials Today Bio)
The integration of chemotherapy and phototherapy for treating advanced liver cancer has gained considerable attention. However, challenges such as short drug retention times significantly impact patient prognosis. We introduce a light-triggered nanosystem that employs molecular aggregation control for PTT and sustained chemotherapy. This nanosystem, known as Reg/IR783@CM nanoparticles (RIMNPs), consists of a core-shell carrier-free nanodrug self-assembled from the chemotherapy drug regorafenib (Reg) and the photothermal agent IR783, coated with a homologous liver cancer cell membrane. The developed core-shell nanocarrier exhibits excellent water dispersibility, high drug load, extended blood circulation, and tumor site enrichment. Upon light exposure, the nanosystem provides outstanding near-infrared imaging and robust photothermal effects. Concurrently, light exposure accelerates the degradation of the outer IR783 layer, resulting in regorafenib exposure and triggering secondary assembly, which significantly enhances drug retention at the tumor site. Our findings indicate that the nanosystem effectively suppresses tumor growth by combining photothermal therapy with the inhibition of tumor cell proliferation and angiogenesis, and by modulating tumor-associated macrophages. Notably, this nanosystem also demonstrates low cytotoxicity and high biocompatibility. This study presents a novel light-driven in-situ assembly strategy, offering a simplified and effective approach for constructing tumor imaging and treatment systems.